Nurture, nature and some very dubious social skills: an interpretative phenomenological analysis of talent identification practices in elite English youth soccer - Miller, P. K.; Cronin, C.; Baker, G. (Qualitative Research in Sport, Exercise and Health, 2015)
This paper reports qualitative findings regarding the concepts and practices utilised in talent identification (TI) among professional coaches working in English youth soccer. Using interpretative phenomenological analysis, detailed interviews with seven such coaches are explored, with a view to elucidating the links between understanding, practice, experience and professional context. Findings reveal three superordinate themes, relating to (1) a primarily `nurtured` and trainable understanding of the broad concept of talent itself, (2) an ostensibly contradictory model of semi-static player psychology, and (3) a highly selective mechanism for separating evidence for `mental strength` and `social skills`. It is contended that these findings underscore a case for more thorough interrogation of the real worlds inhabited by coaches, such that ideas about `good practice` in TI might be more effectively reconciled with grounded knowledge of the practical everyday necessities of being a coach. Volltext auch unter: Nurture, nature and some very dubious social skills: an interpretative phenomenological analysis of talent identification practices in elite English youth soccer